JOHN BRAITHWAITE'S INFLUENCE ON THE INTEGRATED APPROACH IN THE CRIMINAL JUSTICE SYSTEM - AHMAD YUSUF (CV KULTURA DIGITAL MEDIA, 2022)
The criminal justice system can be defined as the use of a systems approach to the administrative mechanism of criminal justice, and criminal justice as a system is the result of the interaction between laws and regulations, administrative practices and social attitudes or behavior. Understanding the system itself implies an interaction process that is prepared rationally and in an efficient manner to provide certain results with all its limitations. According to John Braithwaite, a serious study is needed so that the concept of restorative justice can be applied effectively in the enforcement of cases of violations of tax law, both in terms of violations of administrative provisions and penalties